STRATEGI BUSINESS MODEL CANVAS KELOMPOK TANI MUKTI KOPI DI DESA CIPAGANTI KABUPATEN GARUT - Purwanda, Eka; Herawati, Titin (Manager : Jurnal Ilmu Manajemen, 2022)
Abstract Coffee is one of the main agricultural products that make a significant contribution to the Indonesian economy, namely as a source of foreign exchange earnings, a source of income for farmers, producer of industrial raw materials, job creation and regional development. The Mukti Kopi Cipaganti Farmers Group is a gathering place for all farmers who have plantation land that has not been processed optimally. The problems faced by Cipaganti coffee farmers with the waluya brand are quite complex. On the other hand, the level of coffee productivity is very low compared to other regions in Indonesia. The method used in this study uses a qualitative method called natural research and uses a descriptive analytical method. The strategy formulation technique uses SWOT analysis and Business Model Canvas (BMC) to get an overview of the development of the Mukti Kopi Cipaganti Farmer Group. Market development, market penetration and product development. With the Business Model Canvas (BMC), it supports the development of a sustainability-oriented business model innovation by considering three perspectives, namely economic, environmental and social. Abstrak Kopi merupakan salah satu produk pertanian utama yang memberikan kontribusi signifikan bagi perekonomian Indonesia, yaitu sebagai sumber penerimaan devisa negara, sumber pendapatan petani, penghasil bahan baku industri, penciptaan lapangan kerja dan pembangunan daerah. Kelompok Tani Mukti Kopi Cipaganti merupakan wadah berkumpulnya seluruh petani yang memiliki lahan perkebunan yang belum diolah secara optimal. Permasalahan yang dihadapi petani kopi Cipaganti dengan merek waluya cukup kompleks. Di sisi lain, tingkat produktivitas kopi sangat rendah dibandingkan dengan daerah lain di Indonesia. Metode yang digunakan dalam penelitian ini menggunakan metode kualitatif yang disebut penelitian natural dan menggunakan metode deskriptif analitis. Teknik perumusan strategi menggunakan analisis SWOT dan Business Model Canvas (BMC) untuk mendapatkan gambaran pengembangan Kelompok Tani Mukti Kopi Cipaganti. Pengembangan pasar, penetrasi pasar dan pengembangan produk. Dengan Business Model Canvas (BMC), mendukung pengembangan inovasi model bisnis yang berorientasi keberlanjutan dengan mempertimbangkan tiga perspektif, yaitu ekonomi, lingkungan dan sosial.